Who is the scientist-subject? - Shah, Esha, author.
1 online resource (186 pages).
Keywords: This book explores two disparate sets of debates in the history and philosophy of the life sciences: the history of subjectivity in shaping objective science and the history of dominance of reductionism in molecular biology. It questions the dominant conception of the scientist-subject as a neo-Kantian ideal self –that is, the scientist as a unified and wilful, self-determined, self-regulated, active and autonomous, rational subject wilfully driven by social and scientific ethos –in favour of a narrative that shows how the microcosm of reductionism is sustained, adopted, questioned, or challenged in the creative struggles of the scientist-subject.